Contribution of the initial features of systemic lupus erythematosus to the clinical evolution and survival of a cohort of Mediterranean patients. Issue 9 (15th August 2003) - Buján, S; Ordi-Ros, J; Paredes, J; Mauri, M; Matas, L; Cortés, J; Vilardell, M
Abstract : Background: Systemic lupus erythematosus has a wide spectrum of immunological and clinical manifestations. Its course is characterised by exacerbations which may result in mortality or morbidity to vital organs/systems. Objective: To determine clear and early prognostic markers to avoid further complications. Methods: 245 adult patients diagnosed between January 1978 and March 2001 were studied. Clinical manifestations and laboratory findings both at onset and during the clinical course were collected. The number, type, and severity of the flares were also noted. Statistical analyses between disease features at onset, subsequent flares, and mortality were performed. Results: 239 patients entered the study. Their mean age at onset was 30 years. The mean time between onset and diagnosis was 36 months and the mean evolution time was 114 months. 205 patients developed 915 flares; 205 (22.4%) of these flares were major flares, and affected 110 patients. Cardiac, neurological, or renal affection at onset were associated with a higher probability of developing cardiac (p=0.022), neurological (p<0.001), and renal (p<0.001) exacerbations, respectively, during the evolution. Lupus anticoagulant (LA) and anticardiolipin antibodies (aCL) were predictors of stroke (aCL, p=0.000; LA, p=0.001). Age at diagnosis (p=0.003) and valvular disease at onset (p=0.008) were independent predictors of low survival. Conclusions: Renal, cardiac, or neurological involvement and the presence of LA or aCL positivity at onset were predictors of renal, cardiac, or neurological flares, respectively. Age and valvular involvement at onset were found to be independent adverse outcome predictors for low survival.